Science is the fuel required for lifting ecosystem restoration into the orbit of hundreds of millions of hectares - Mills, Anthony J.; Duker, Robbert; Lechmere-Oertel, Richard G.; van Mazijk, Ruan; Potts, Alastair J. (Frontiers in Conservation Science, 2023)
Restoring the hundreds of millions of hectares of degraded ecosystems worldwide will require new approaches to raise the required funds and new systems to implement at the required scales. Two decades of large-scale restoration in the subtropical thicket biome in the Eastern Cape, South Africa, have generated valuable information for developing such approaches and systems. The successful upscaling of restoration in this biome can be attributed to four main actions. First, from the outset in 2003, peer-reviewed science was foundational to the entire restoration initiative. Second, also from the outset, there was a commitment to large-scale, long-term ecological research by the public sector (the then Department of Water Affairs and Forestry in South Africa), which resulted in ostensibly the world's largest ecosystem restoration experiment, comprising 330 quarter-hectare plots distributed over ~75,000 km2 . Third, retrospective scientific description of previous restoration work - done by farmers in the 1960s and 1970s - provided valuable information on restoration's multiple benefits, without having to wait for the large-scale restoration experiment to yield results. Lastly, diverse and short-term scoping studies were undertaken to address questions that emerged during the large-scale implementation of restoration. These studies were vital for rapid adaptive management and planning new scientific experiments, filling a gap between long-term ecological research and retrospective science.